2021
DOI: 10.1200/jco.2021.39.6_suppl.487
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of immune checkpoint blockade in patients with advanced upper tract urothelial cancer and mismatch repair deficiency or microsatellite instability (MSI).

Abstract: 487 Background: Tumors deficient in DNA mismatch repair (dMMR) exhibit a microsatellite unstable phenotype characterized by high tumor mutational burden and an immunogenic tumor microenvironment. Despite the histology-agnostic approval of pembrolizumab for advanced dMMR/MSI cancers, responsiveness of dMMR/MSI upper tract urothelial cancers (UTUC) to immune checkpoint (IC) blockade remains largely unknown. Methods: Consecutive records of patients (pts) from a single institution with locally advanced unresectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We found that dMMR and MSI-H metastatic UC is responsive to ICI, with included studies reporting ORRs of 50%–90%, 35 36 39 101 deep responses 35 36 39 101 121 126 164 and long durations of response 121 123 126 132 ( online supplemental tables S3 and S4 ). These data show that dMMR and MSI-H may be predictive biomarkers for response to ICI in UC, which has already been prospectively demonstrated in solid tumours.…”
Section: Discussionmentioning
confidence: 94%
“…We found that dMMR and MSI-H metastatic UC is responsive to ICI, with included studies reporting ORRs of 50%–90%, 35 36 39 101 deep responses 35 36 39 101 121 126 164 and long durations of response 121 123 126 132 ( online supplemental tables S3 and S4 ). These data show that dMMR and MSI-H may be predictive biomarkers for response to ICI in UC, which has already been prospectively demonstrated in solid tumours.…”
Section: Discussionmentioning
confidence: 94%
“…Microsatellite instability, DNA mismatch repair status, and tumor mutational burden have also been associated with response to immunotherapy [ 13 , 102 ]. A classic example of the identification of relevant genetic signatures is the relation between high interferon gamma expression and response to nivolumab in CheckMate 275 [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with alterations in epigenetic modifiers, such as KDM6A and ARID1A, can benefit from trials of EZH2 inhibitors. Patients with tumors showing high microsatellite instability, high TMB or deficient mismatch repair, might benefit more from enrollment in immunotherapy trials [ 102 ]. Although not compared head-to-head with EVP in patients with FGFR alterations, the combination of erdafitinib plus cetrelimab in the NORSE trial showed an ORR of 54.5% and a median OS of 20.8 months [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the phase 2 mono-arm TROPHY-U-01, 113 patients with metastatic UC and disease progression after prior platinum-based and anti PD(L)-1 therapies were allocated to receive sacituzumab govitecan, an anti-Trop2 antibody conjugated to SN-38 (an active metabolite of irinotecan) [84]. While the inclusion criteria allowed for the admission of patients with UTUC, no data for this population have been published.…”
Section: Trop-2mentioning
confidence: 99%